Supported lithium hexafluorosilicate and preparation method thereof, graphite negative electrode sheet and preparation method thereof and application thereof
By applying porous inorganic compound carriers to grow lithium hexafluorosilicate in situ on the graphite negative electrode sheet, the problem of insufficient fast charging capability and cycle stability of graphite negative electrode in lithium-ion batteries is solved, and higher ion transmission rates and better battery performance are achieved.
Patent Information
- Application Number
- CN202411605122.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The fast charging capability and cycle stability of graphite negative electrodes in lithium-ion batteries are insufficient, and there are safety hazards.
By growing lithium hexafluorosilicate in situ on a porous inorganic compound carrier and applying it to graphite negative electrode sheets, its fast charging ability and cycle stability are improved.
This method effectively accelerates the ion transmission rate, improves the fast charging performance and cycle stability of the graphite negative electrode sheet, and reduces safety hazards.
Smart Images

Figure CN119143137B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage technology, and in particular to a supported lithium hexafluorosilicate and a preparation method thereof, a graphite negative electrode sheet and a preparation method and application thereof. Background Art
[0002] At present, lithium-ion batteries with graphite as negative electrodes have excellent electrochemical performance and cost advantages, but are limited by the layered structure of graphite itself and the solvation of lithium ions, resulting in a slow ion transfer rate of the graphite negative electrode, which limits the fast charging capability of the entire lithium-ion battery, and at the same time, there are serious safety hazards in long-term cycles. In order to improve the fast charging capability of graphite negative electrodes, the existing technology improves the ion transfer rate and fast charging performance of graphite negative electrodes by means of graphite negative electrode doping design, surface chemical modification, etc. However, these methods will objectively increase the reaction activity of the negative electrode surface, and in the long-term fast charging cycle process, it will cause irreversible lithium accumulation at the negative electrode or continuous refreshing and thickening of the surface SEI film, which seriously damages the lithium-ion battery. Summary of the invention
[0003] Based on this, it is necessary to provide a loaded lithium hexafluorosilicate and its preparation method, a graphite negative electrode sheet and its preparation method and application to address the above problems. By in-situ growing lithium hexafluorosilicate on a porous inorganic compound carrier, it can effectively improve the fast charging capability and cycle stability when applied to a graphite negative electrode sheet.
[0004] A method for preparing supported lithium hexafluorosilicate comprises the following steps:
[0005] Under an inert atmosphere, a porous inorganic compound carrier and a lithium hexafluorosilicate precursor are placed in a non-aqueous solvent, and the pH is adjusted to react under acidic conditions, so that the lithium hexafluorosilicate precursor reacts in situ on the porous inorganic compound carrier to generate lithium hexafluorosilicate, and after the reaction is completed, the supported lithium hexafluorosilicate is separated.
[0006] In one embodiment, the mass fraction of lithium hexafluorosilicate in the supported lithium hexafluorosilicate is 30%-70%.
[0007] In one embodiment, the porous inorganic compound carrier further satisfies at least one of the following conditions:
[0008] (1) The porous inorganic compound carrier is selected from at least one of a porous SiO carrier, a porous SiO2 carrier, a porous Sb2O3 carrier, a porous Al2O3 carrier, a porous TiO2 carrier, a porous MoO2 carrier, a porous MoO3 carrier, a porous MgO carrier, a porous silicate carrier, a porous aluminate carrier or a porous titanate carrier;
[0009] (2) D of the porous inorganic compound carrier50 The particle size is 5μm-20μm, and the specific surface area is 1000m 2 / g-2000m 2 / g, pore volume 0.5cm 3 / g-1.5cm 3 / g, pore size is 1nm-10nm;
[0010] (3) Before placing the porous inorganic compound support in a non-aqueous solvent, the porous inorganic compound support is subjected to a calcination treatment, an acid washing treatment, and a water washing treatment in sequence.
[0011] In one embodiment, the non-aqueous solvent is selected from aprotic solvents.
[0012] In one embodiment, during the reaction, the pH is 4-6 and the temperature is 70°C-120°C.
[0013] The present invention also provides supported lithium hexafluorosilicate prepared by the preparation method of supported lithium hexafluorosilicate.
[0014] The present invention also provides a graphite negative electrode sheet, comprising a current collector and a graphite material layer attached to the surface of the current collector, wherein the surface of the graphite material layer is also attached with the supported lithium hexafluorosilicate.
[0015] In one embodiment, the amount of the supported lithium hexafluorosilicate is 1 to 10 times the mass of graphite in the graphite material layer.
[0016] The present invention also provides a method for preparing the graphite negative electrode sheet, comprising the following steps:
[0017] Providing a prefabricated graphite negative electrode sheet, the prefabricated graphite negative electrode sheet comprising a current collector and a graphite material layer attached to a surface of the current collector;
[0018] The supported lithium hexafluorosilicate is dispersed in a non-aqueous solvent to obtain a dispersion, and the dispersion is placed on the surface of the graphite material layer of the prefabricated graphite negative electrode sheet, and dried to obtain a graphite negative electrode sheet.
[0019] The present invention also provides a lithium ion battery, comprising the graphite negative electrode sheet.
[0020] In the present invention, after in-situ synthesis of lithium hexafluorosilicate on the surface or in the pores of a porous inorganic compound carrier, the obtained supported lithium hexafluorosilicate has a multi-level pore structure, which not only has excellent ion adsorption performance, but also the interconnectivity of its multi-level pores provides a rich transmission channel for ions, effectively shortens the transmission distance of ions, accelerates the transmission rate of ions, and then when it is applied to a graphite negative electrode sheet, it can effectively improve the fast charging ability and cycle stability of the graphite negative electrode sheet. In addition, there is good interfacial adhesion between the supported lithium hexafluorosilicate and the graphite negative electrode material, which can not only make the electrolyte fully infiltrated, but also avoid the occurrence of excessive side reactions between the electrode and the electrolyte, which can not only effectively promote the formation of a stable interface protective layer at the electrode / electrolyte interface, improve the cycle stability of the battery, but also effectively improve the ionic conductivity of the graphite negative electrode sheet and improve the fast charging performance of the graphite negative electrode sheet.
[0021] Therefore, when the supported lithium hexafluorosilicate prepared by the present invention is applied to a graphite negative electrode sheet, the fast charging capability and cycle stability can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 These are two EIS test spectra of the button cell installed in Example 3 before cycling;
[0024] Figure 2 Two EIS test spectra of the button cell installed in Application Example 3 cycled 500 times at 4C;
[0025] Figure 3 The cycle curve diagram of the button cell installed in Application Example 3 after 500 cycles at 4C, wherein A is the charging curve and B is the discharging curve;
[0026] Figure 4 Two EIS test spectra of the button cell installed in Comparative Example 1 before cycling;
[0027] Figure 5 Two EIS test spectra of the button cell installed in Comparative Example 1 cycled 500 times at 4C, where A is the charging curve and B is the discharging curve;
[0028] Figure 6 The cycle curve diagram of the button cell installed in Comparative Example 1 after 500 cycles at 4C, wherein A is the charging curve and B is the discharging curve;
[0029] Figure 7 The figure is a cycle curve diagram of the button-type battery of comparative example 3 cycled 200 times at 4C, wherein A is the charging curve and B is the discharging curve. DETAILED DESCRIPTION
[0030] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0032] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0033] The preparation method of supported lithium hexafluorosilicate provided by the present invention comprises the following steps: placing a porous inorganic compound carrier and a lithium hexafluorosilicate precursor in a non-aqueous solvent under an inert atmosphere, adjusting the pH to an acidic condition for reaction, so that the lithium hexafluorosilicate precursor reacts in situ on the porous inorganic compound carrier to generate lithium hexafluorosilicate, and separating to obtain supported lithium hexafluorosilicate after the reaction is completed.
[0034] In the preparation method of the present invention, when the pH is adjusted to react under acidic conditions, the lithium hexafluorosilicate precursor will in situ synthesize lithium hexafluorosilicate on the surface or in the pores of the porous inorganic compound carrier, so that the obtained supported lithium hexafluorosilicate has a multi-level pore structure, which not only has excellent ion adsorption performance, but also the interconnectivity of the multi-level pores provides abundant transmission channels for ions, effectively shortens the transmission distance of ions, and accelerates the transmission rate of ions.
[0035] Optionally, the mass fraction of lithium hexafluorosilicate in the supported lithium hexafluorosilicate is 30%-70%, which is conducive to further optimizing the pore structure of the supported lithium hexafluorosilicate, thereby being more conducive to accelerating the ion transmission rate. It is understood that the amount of lithium hexafluorosilicate precursor can be calculated by presetting the mass fraction of lithium hexafluorosilicate in the supported lithium hexafluorosilicate.
[0036] Wherein, the porous inorganic compound carrier is selected from at least one of a porous SiO carrier, a porous SiO2 carrier, a porous Sb2O3 carrier, a porous Al2O3 carrier, a porous TiO2 carrier, a porous MoO2 carrier, a porous MoO3 carrier, a porous MgO carrier, a porous silicate carrier, a porous aluminate carrier or a porous titanate carrier; the lithium hexafluorosilicate precursor includes a silicon source, a lithium source and a fluorine source, the silicon source is selected from at least one of SiO, SiO2, Li2SiO3, siloxane (PDMS), tetraethyl orthosilicate (TEOS) or vinyl silane, and the lithium source and fluorine source are selected from at least one of lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), ammonium hexafluorophosphate (NH4PF6), lithium difluorophosphate (LiPF2O2), lithium difluoroborate oxalate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethanesulfonyl)imide.
[0037] Optionally, the D of the porous inorganic compound carrier 50 The particle size is 5 μm-20 μm, including but not limited to 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm; the specific surface area is 1000 m 2 / g-2000m 2 / g, including but not limited to 1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m2 / g、1900m 2 / g or 2000m 2 / g; pore volume is 0.5cm 3 / g-1.5cm 3 / g, including but not limited to 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g or 1.5cm 3 / g; the pore size is 1nm-10nm, including but not limited to 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm or 10nm. Such a setting is more conducive to obtaining a supported lithium hexafluorosilicate with a multi-level pore structure, which is more conducive to the transmission rate of ions.
[0038] Furthermore, before placing the porous inorganic compound carrier in a non-aqueous solvent, the porous inorganic compound carrier is preferably pretreated to remove impurities in the porous inorganic compound carrier and to better expose the pores of the porous inorganic compound carrier, thereby increasing the activation degree, facilitating the in-situ synthesis of lithium hexafluorosilicate, and increasing the loading rate.
[0039] Optionally, the pretreatment step includes calcination and pickling, followed by water washing to neutrality. The calcination temperature is 300°C-700°C, including but not limited to 300°C, 400°C, 500°C, 600°C or 700°C, and the calcination time is 1h-4h, including but not limited to 1h, 2h, 3h or 4h; the acid used in the pickling is at least one of dilute hydrochloric acid or dilute nitric acid, the concentration of the acid is 0.1mol / L-0.5mol / L, including but not limited to 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L or 0.5mol / L, and the pickling time is 1h-2h.
[0040] Optionally, when the pH is adjusted to react under acidic conditions, the pH is preferably 4-6, and the temperature is preferably 70°C-120°C, including but not limited to 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, so as to help inhibit hydrolysis and promote the reaction, wherein the pH can be adjusted using at least one of dilute hydrochloric acid, hydrofluoric acid, dilute nitric acid or dilute sulfuric acid.
[0041] Furthermore, the non-aqueous solvent is preferably an aprotic solvent, including but not limited to at least one of petroleum ether, benzene, n-pentylbenzene, n-pentyl benzoate, carbon tetrachloride, dichloromethane, perfluoroheptane, carbon disulfide or hexafluoroisobutylene, which neither produces water nor reacts under acidic conditions.
[0042] It can be understood that the present invention has no special requirements for the inert atmosphere, and the inert atmosphere can be selected from at least one of nitrogen, argon, and a hydrogen-argon mixed gas.
[0043] The present invention also provides a supported lithium hexafluorosilicate prepared by the preparation method of supported lithium hexafluorosilicate, which has a multi-level interconnected pore structure, not only has excellent ion adsorption, but also can provide more ion transmission channels, shorten the ion transmission distance, and accelerate its transmission rate, thereby improving ion conductivity.
[0044] The present invention also provides a graphite negative electrode sheet, comprising a current collector and a graphite material layer attached to the surface of the current collector, the surface of the graphite material layer also having the supported lithium hexafluorosilicate attached thereto. The graphite material layer is made of graphite, a binder, a conductive agent, etc. in proportion.
[0045] Optionally, the amount of the supported lithium hexafluorosilicate used is 1 to 10 times the mass of graphite in the graphite material layer.
[0046] The surface of the graphite negative electrode sheet prepared by the present invention has loaded lithium hexafluorosilicate. The loaded lithium hexafluorosilicate not only has excellent ion adsorption performance, but also the interconnectedness of its multi-level pores provides abundant transmission channels for ions, effectively shortens the transmission distance of ions, and accelerates the transmission rate of ions, thereby effectively improving the fast charging capability and cycle stability of the graphite negative electrode sheet.
[0047] In addition, the loaded lithium hexafluorosilicate and the graphite negative electrode material have good interfacial adhesion, which can not only allow the electrolyte to fully infiltrate, but also avoid the occurrence of excessive side reactions between the electrode and the electrolyte. It can not only effectively promote the formation of a stable interface protection layer at the electrode / electrolyte interface and improve the cycle stability of the battery, but also effectively improve the ionic conductivity of the graphite negative electrode sheet and improve the fast charging performance of the graphite negative electrode sheet.
[0048] Therefore, the graphite negative electrode sheet of the present invention can effectively improve the fast charging capability and cycle stability.
[0049] The present invention also provides a method for preparing the graphite negative electrode sheet, comprising the following steps:
[0050] S1, providing a prefabricated graphite negative electrode sheet, wherein the prefabricated graphite negative electrode sheet comprises a current collector and a graphite material layer attached to a surface of the current collector;
[0051] S2, dispersing supported lithium hexafluorosilicate in a non-aqueous solvent to obtain a dispersion, placing the dispersion on the surface of the graphite material layer of the prefabricated graphite negative electrode sheet, and obtaining a graphite negative electrode sheet after drying.
[0052] It can be understood that the prefabricated graphite negative electrode sheet in step S1 is a traditional graphite negative electrode sheet, which is prepared by mixing components such as graphite, a conductive agent and a binder to form a slurry, and then coating the slurry on a current collector and drying and slicing it. The present invention mainly uses supported lithium hexafluorosilicate to treat the traditional graphite negative electrode sheet to improve the fast charging performance and electrochemical properties of the graphite negative electrode sheet.
[0053] Optionally, the non-aqueous solvent described in step S2 is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, dimethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, acetonitrile, butyronitrile, benzonitrile, ethanedinitrile or acrylonitrile, and the dispersion is placed on the surface of the graphite material layer of the prefabricated graphite negative electrode sheet by coating, dripping, etc.
[0054] The present invention also provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the graphite negative electrode sheet, thereby effectively improving the fast charging capability and cycle stability.
[0055] Hereinafter, the supported lithium hexafluorosilicate and its preparation method, the graphite negative electrode sheet and its preparation method and application will be further described through the following specific examples.
[0056] Example 1
[0057] D 50 The particle size is 5 μm and the specific surface area is 1284.6 m 2 / g, pore volume is 0.5cm 3 / g, and a porous SiO2 carrier with a pore size of 8.23nm was heated to 300°C at a rate of 5°C / min in an air atmosphere and kept warm for 1h. Then, it was immersed in 0.1mol / L dilute hydrochloric acid, pickled at 70°C for 1h, washed with water until neutral, and dried to obtain a pretreated porous SiO2 carrier.
[0058] Under argon atmosphere, 1 g of pretreated porous SiO carrier was placed in 30 ml of benzene, and 2 g of LiBF4 and 1 g of SiO were added thereto, and then dilute hydrochloric acid was added dropwise to control the pH to 4, and stirred at 80 ° C for 8 h. After the reaction was completed, centrifugation and washing with acetonitrile solvent were performed, and then vacuum drying was performed to obtain porous SiO supported lithium hexafluorosilicate.
[0059] Example 2
[0060] D 50 The particle size is 5 μm and the specific surface area is 1468.4 m 2 / g, pore volume is 0.65cm 3 / g, a porous SiO2 carrier with a pore size of 6.52nm, was heated to 300℃ at a rate of 5℃ / min in an air atmosphere and kept warm for 1h. Then, it was immersed in 0.1mol / L dilute hydrochloric acid, pickled at 70℃ for 1h, washed with water to neutrality, and dried to obtain a pretreated porous SiO2 carrier.
[0061] Under argon atmosphere, 2g of pretreated porous SiO2 carrier was placed in 30ml of petroleum ether, and 2g of LiPF6 and 1g of SiO2 were added thereto, and then hydrofluoric acid was added dropwise to control the pH of the solvent to 6. The mixture was stirred at 80°C for 10h. After the reaction was completed, it was centrifuged and washed with acetonitrile several times, and then vacuum dried to obtain porous SiO2-loaded lithium hexafluorosilicate.
[0062] Example 3
[0063] D 50 The particle size is 8μm and the specific surface area is 1468.4m 2 / g, pore volume is 0.65cm 3 / g, a porous SiO2 carrier with a pore size of 6.52nm, was heated to 500℃ at a rate of 5℃ / min in an air atmosphere and kept warm for 2h. Then, it was immersed in 0.2mol / L dilute hydrochloric acid, pickled at 70℃ for 1h, washed with water to neutrality, and dried to obtain a pretreated porous SiO2 carrier.
[0064] Under argon atmosphere, 2 g of pretreated porous SiO2 carrier was placed in 30 ml of perfluoroheptane, and 4 g of LiPF6 and 2 g of SiO2 were added thereto, and then hydrofluoric acid was added dropwise to control the pH of the solvent to 6. The mixture was stirred at 100 °C for 15 h. After the reaction was completed, it was centrifuged and washed with acetonitrile several times, and then vacuum dried to obtain porous SiO2-loaded lithium hexafluorosilicate.
[0065] Example 4
[0066] D 50 The particle size is 8μm and the specific surface area is 1523.6m 2 / g, pore volume is 0.69cm 3 / g, a porous Mo2O3 carrier with a pore size of 6.34nm, was heated to 500℃ at a rate of 5℃ / min in an air atmosphere and kept warm for 2h. Then, it was immersed in 0.2mol / L dilute hydrochloric acid, pickled at 70℃ for 1h, washed with water to neutrality, and dried to obtain a pretreated porous Mo2O3 carrier.
[0067] Under argon atmosphere, 2 g of pretreated porous Mo2O3 carrier was placed in 30 ml of perfluoroheptane, and 6 g of NH4PF6 and 4 g of Li2SiO3 were added thereto, and then dilute sulfuric acid was added dropwise to control the pH of the solvent to 5. The mixture was stirred at 100°C for 15 h. After the reaction was completed, it was centrifuged and washed several times with acetonitrile solvent, and then vacuum dried to obtain porous Mo2O3-loaded lithium hexafluorosilicate.
[0068] Example 5
[0069] D 50 The particle size is 8μm and the specific surface area is 1523.6m 2 / g, pore volume is 0.69cm 3 / g, and a porous Mo2O3 with a pore size of 6.34nm, was heated to 700℃ at a rate of 5℃ / min in an air atmosphere and kept warm for 2h. Then, it was immersed in 0.2mol / L dilute hydrochloric acid, pickled at 70℃ for 1h, washed with water to neutrality, and dried to obtain a pretreated porous Mo2O3 carrier.
[0070] Under argon atmosphere, 2 g of pretreated porous Mo2O3 carrier was placed in 30 ml of perfluoroheptane, and 6 g of NH4PF6 and 4 g of Li2SiO3 were added thereto, and then dilute sulfuric acid was added dropwise to control the pH of the solvent to 5. The mixture was stirred at 100 °C for 15 h. After the reaction was completed, it was centrifuged and washed several times with dimethyl carbonate, and then vacuum dried to obtain porous Mo2O3-loaded lithium hexafluorosilicate.
[0071] Example 6
[0072] D 50 The particle size is 8μm and the specific surface area is 1578.9m 2 / g, pore volume is 0.71cm 3 / g, a porous Al2O3 carrier with a pore size of 6.18nm, was heated to 500℃ at a rate of 5℃ / min in an air atmosphere and kept warm for 2h. Then, it was immersed in 0.2mol / L dilute hydrochloric acid, pickled at 70℃ for 1h, washed with water to neutrality, and dried to obtain a pretreated porous Al2O3 carrier.
[0073] Under argon atmosphere, 2 g of pre-treated porous Al2O3 carrier was placed in 30 ml of carbon tetrachloride, and 4 g of lithium difluorophosphate and 2 g of siloxane were added thereto, and then dilute nitric acid was added dropwise to control the pH of the solvent to 4.5. The mixture was stirred at 100°C for 15 hours. After the reaction was completed, it was centrifuged and washed several times with acetonitrile solvent, and then vacuum dried to obtain porous Al2O3-loaded lithium hexafluorosilicate.
[0074] Example 7
[0075] D 50The particle size is 8μm and the specific surface area is 1578.9m 2 / g, pore volume is 0.71cm 3 / g, a porous Al2O3 carrier with a pore size of 6.18nm, was heated to 500℃ at a rate of 5℃ / min in an air atmosphere and kept warm for 2h. Then, it was immersed in 0.2mol / L dilute hydrochloric acid, pickled at 70℃ for 1h, washed with water to neutrality, and dried to obtain a pretreated porous Al2O3 carrier.
[0076] Under argon atmosphere, 2 g of pretreated porous Al2O3 carrier was placed in 30 ml of carbon tetrachloride, and 4 g of lithium oxalate difluoroborate and 2 g of tetraethyl orthosilicate were added thereto, and then dilute nitric acid was added dropwise to control the pH of the solvent to 4.5. The mixture was stirred at 100°C for 15 h. After the reaction was completed, it was centrifuged and washed with acetonitrile several times, and then vacuum dried to obtain porous Al2O3-loaded lithium hexafluorosilicate.
[0077] Comparative Example 1
[0078] Under argon atmosphere, 4g of LiPF6 and 2g of SiO2 were placed in 30ml of perfluoroheptane, and then hydrofluoric acid was added dropwise to control the pH of the solvent to 6. The mixture was stirred at 100°C for 15h. After the reaction was completed, it was centrifuged and washed several times with acetonitrile, and then vacuum dried to obtain lithium hexafluorosilicate.
[0079] Comparative Example 2
[0080] Under argon atmosphere, 4 g of lithium oxalodifluoroborate and 2 g of tetraethyl orthosilicate were placed in 30 ml of carbon tetrachloride, and then dilute nitric acid was added dropwise to control the pH of the solvent to 4.5. The mixture was stirred at 100 °C for 15 h. After the reaction was completed, the mixture was centrifuged and washed several times with acetonitrile, and then vacuum dried to obtain lithium hexafluorosilicate.
[0081] Blank Application Example
[0082] Weigh 320 mg of artificial graphite material, 40 mg of conductive carbon black and 40 mg of carboxymethyl cellulose, add appropriate amount of deionized water and use planetary ball mill for 2 h, apply the milled slurry on the current collector, and cut it into graphite negative electrode sheets with a diameter of 12 mm after vacuum drying at 80 ° C for 12 h. The loading is 2.5 mg / cm 2 .
[0083] Then, metallic lithium was used as the counter electrode and reference electrode, PP membrane was selected as the diaphragm, LiPF6 with a concentration of 1 mol / L was used as the electrolyte, and the solvent was a mixed solution of diethyl carbonate and ethylene carbonate with a volume ratio of 1:1. The button battery was assembled in a glove box with an argon atmosphere.
[0084] Application Example 1
[0085] The difference between Application Example 1 and the Application Blank Example is that the supported lithium hexafluorosilicate prepared in Example 1 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of the supported lithium hexafluorosilicate to the solvent is 1:1, and then dripped onto the surface of the graphite negative electrode sheet in an amount of 100 μl.
[0086] Application Example 2
[0087] The difference between Application Example 2 and the Application Blank Example is that the supported lithium hexafluorosilicate prepared in Example 2 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of the supported lithium hexafluorosilicate to the solvent is 1:1, and then dripped onto the surface of the graphite negative electrode sheet in an amount of 300 μl.
[0088] Application Example 3
[0089] The difference between Application Example 3 and the Application Blank Example is that the supported lithium hexafluorosilicate prepared in Example 3 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of the supported lithium hexafluorosilicate to the solvent is 1:1, and then dripped on the surface of the graphite negative electrode sheet in an amount of 500 μl.
[0090] Application Example 4
[0091] The difference between Application Example 4 and the Application Blank Example is that the supported lithium hexafluorosilicate prepared in Example 4 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of the supported lithium hexafluorosilicate to the solvent is 1:1, and then dripped onto the surface of the graphite negative electrode sheet in an amount of 500 μl.
[0092] Application Example 5
[0093] The difference between Application Example 5 and the Application Blank Example is that the supported lithium hexafluorosilicate prepared in Example 5 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of the supported lithium hexafluorosilicate to the solvent is 1:1, and then dripped onto the surface of the graphite negative electrode sheet in an amount of 1000 μl.
[0094] Application Example 6
[0095] The difference between Application Example 6 and the Application Blank Example is that the supported lithium hexafluorosilicate prepared in Example 6 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of the supported lithium hexafluorosilicate to the solvent is 1:1, and then dripped on the surface of the graphite negative electrode sheet in an amount of 500 μl.
[0096] Application Example 7
[0097] The difference between Application Example 7 and the Application Blank Example is that the supported lithium hexafluorosilicate prepared in Example 7 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of the supported lithium hexafluorosilicate to the solvent is 1:1, and then dripped on the surface of the graphite negative electrode sheet in an amount of 500 μl.
[0098] Application Comparative Example 1
[0099] The difference between the comparative example 1 and the blank example is that the lithium hexafluorosilicate prepared in the comparative example 1 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of lithium hexafluorosilicate to the solvent is 1:1, and then dripped on the surface of the graphite negative electrode sheet in an amount of 500 μl.
[0100] Application Comparative Example 2
[0101] The difference between the comparative example 2 and the blank example is that the lithium hexafluorosilicate prepared in the comparative example 2 is uniformly dispersed in a dimethyl carbonate and ethylene carbonate solvent mixed in a volume ratio of 1:1, wherein the molar ratio of lithium hexafluorosilicate to the solvent is 1:1, and then dripped on the surface of the graphite negative electrode sheet in an amount of 500 μl.
[0102] The electrochemical performance test of the button cell obtained above was carried out on the Xinwei battery test system. The charge and discharge voltage range was 0.005V-2V, the current density was 0.1C, 1C=372mA / g, and the test results were as follows: Figures 1 to 7 And as shown in Table 1.
[0103] Table 1
[0104]
[0105] Combination Figures 1 to 7 As shown in Table 1, after the porous inorganic compound is loaded with lithium hexafluorosilicate, the specific surface area increases significantly and the average pore size decreases significantly, indicating that the loaded lithium hexafluorosilicate has a multi-level pore structure. When used in batteries, it shows higher ionic conductivity before and after the battery cycle, and has better charge and discharge performance, which can effectively improve the fast charging performance and cycle stability.
[0106] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing supported lithium hexafluorosilicate, characterized in that: The following steps are involved: Under an inert atmosphere, a porous inorganic compound carrier and a lithium hexafluorosilicate precursor are placed in a non-aqueous solvent, and the pH is adjusted to react under acidic conditions, so that the lithium hexafluorosilicate precursor reacts in situ on the porous inorganic compound carrier to generate lithium hexafluorosilicate, and after the reaction is completed, the supported lithium hexafluorosilicate is separated, wherein the lithium hexafluorosilicate precursor includes a silicon source, a lithium source and a fluorine source, the silicon source is selected from at least one of SiO, SiO2, Li2SiO3, siloxane, tetraethyl orthosilicate or vinyl silane, and the lithium source and the fluorine source are selected from at least one of lithium tetrafluoroborate, lithium hexafluorophosphate, ammonium hexafluorophosphate, lithium difluorophosphate, lithium oxalate difluoroborate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethanesulfonyl)imide.
2. The method for preparing supported lithium hexafluorosilicate according to claim 1, characterized in that: The mass fraction of lithium hexafluorosilicate in the supported lithium hexafluorosilicate is 30%-70%.
3. The method for preparing supported lithium hexafluorosilicate according to claim 1, characterized in that: The porous inorganic compound carrier also satisfies at least one of the following conditions: (1) The porous inorganic compound carrier is selected from at least one of a porous SiO carrier, a porous SiO2 carrier, a porous Sb2O3 carrier, a porous Al2O3 carrier, a porous TiO2 carrier, a porous MoO2 carrier, a porous MoO3 carrier, a porous MgO carrier, a porous silicate carrier, a porous aluminate carrier or a porous titanate carrier; (2) D of the porous inorganic compound carrier 50 The particle size is 5μm-20μm, and the specific surface area is 1000m 2 / g-2000m 2 / g, pore volume 0.5cm 3 / g-1.5cm 3 / g, pore size is 1nm-10nm; (3) Before placing the porous inorganic compound support in a non-aqueous solvent, the porous inorganic compound support is subjected to a calcination treatment, an acid washing treatment, and a water washing treatment in sequence.
4. The method for preparing supported lithium hexafluorosilicate according to claim 1, characterized in that: The non-aqueous solvent is selected from aprotic solvents.
5. The method for preparing supported lithium hexafluorosilicate according to claim 1, characterized in that: During the reaction, the pH is 4-6 and the temperature is 70°C-120°C.
6. A supported lithium hexafluorosilicate prepared by the method for preparing supported lithium hexafluorosilicate according to any one of claims 1 to 5.
7. A graphite negative electrode sheet, characterized in that: It comprises a current collector and a graphite material layer attached to the surface of the current collector, wherein the surface of the graphite material layer is also attached with the supported lithium hexafluorosilicate as claimed in claim 6.
8. The graphite negative electrode sheet according to claim 7, characterized in that: The amount of the supported lithium hexafluorosilicate used is 1 to 10 times the mass of the graphite in the graphite material layer.
9. A method for preparing a graphite negative electrode sheet according to claim 7 or claim 8, characterized in that: The following steps are involved: Providing a prefabricated graphite negative electrode sheet, the prefabricated graphite negative electrode sheet comprising a current collector and a graphite material layer attached to a surface of the current collector; The supported lithium hexafluorosilicate is dispersed in a non-aqueous solvent to obtain a dispersion, and the dispersion is placed on the surface of the graphite material layer of the prefabricated graphite negative electrode sheet, and dried to obtain a graphite negative electrode sheet.
10. A lithium ion battery, characterized in that: Comprising the graphite negative electrode sheet as claimed in claim 7 or claim 8.
Citation Information
Patent Citations
Anode active material for lithium storage battery and lithium storage battery having the same
CN101872861A
Alpha-alumina carrier, preparation method, silver catalyst and application
CN114425373A